(untitled) (Journal of Pathology of Nepal, 2015)
Malignant mucosal melanoma is very rare entity. It comprises about 1% of all malignant melanoma and exhibit more aggressive behaviour than that of skin melanomas. Mucosal melanoma arises mainly from the mucous membranes of head and neck, the female genital organs or the anorectal and the urinary tracts. Laryngeal malignant melanoma constitutes 3.8% to 7.4% of all cases of malignant mucosal melanoma of head and neck. In this article we report a case of primary malignant mucosal melanoma of larynx in 27 years old male who was treated with radical surgery and adjuvant chemotherapy in BPKM Cancer Hospital, Chitwan.